Congenital generalized congenital lipodystrophy type 2 in the Moche culture - Purizaca-Rosillo, Nelson (2023)
The Moche artist are among the most outstanding plastic representatives in the central Andes during the pre-Hispanic era, within this scenario, we could analyze a sculptural ceramic piece (code C-1335) recorded in the Huaca de la Luna archaeological site in Trujillo, Perú. The vessel corresponds to two individuals with morphological characteristics that allow them to be associated with type 2 congenital generalized lipodystrophy. Considering the geographical, the physical features, and the current cases of this disease, allow us to indicate that people with generalized congenital lipodystrophy probably existed in Mochica society during pre-Hispanic times.